Analysis Of Factors And Strategies In Overcoming Reading Difficulties In Elementary Students - Elsa Aprilla; Seri Hartati (Journal of Sustainable Education, 2026)
This study aims to examine the causes of reading difficulties and the strategies used to address them among students in higher grades of elementary school. The research was conducted using a qualitative descriptive approach through methods such as interviews, observations, documentation, and literature review. The research results show that reading difficulties are shown through slow reading, mistakes in recognizing letters and sounds, and a low understanding of the reading material. The causes come from inside, like low motivation, limited vocabulary, memory problems, and poor psychological condition, as well as from outside, such as lack of family support, limited learning facilities, and unsuitable teaching methods. The strategy involves using technology-based phonics learning, giving extra reading time, working together between teachers and parents, and providing reading materials that match each student's characteristics